A single-step sizing and radiofrequency ablation catheter for circumferential ablation of Barrett's esophagus: Results of a pilot study - Belghazi, K (United European Gastroenterol J, 2018)
BACKGROUND: The 360 Express balloon catheter (360 Express) has the ability to self-adjust to the esophageal lumen, ensuring optimal tissue contact. OBJECTIVE: The objective of this article is to evaluate the efficacy and safety of the 360 Express for radiofrequency ablation (RFA) treatment of Barrett's esophagus (BE). METHODS: BE patients with low-grade dysplasia (LGD), high-grade dysplasia (HGD) or early cancer (EC) were included. Visible lesions were removed by endoscopic resection (ER) prior to RFA. RFA was performed with the 360 Express using the standard ablation regimen (12J/cm(2)–clean–12J/cm(2)). Primary outcome: BE regression percentage at three months. Secondary outcomes: procedure time, adverse events, complete eradication of dysplasia (CE-D) and intestinal metaplasia (CE-IM). RESULTS: Thirty patients (median BE C4M6) were included. Eight patients underwent ER prior to RFA. Median BE regression: 90%. Median procedure time: 31 minutes. Adverse events (13%): laceration (n = 1); atrial fibrillation (n = 1); vomiting and dysphagia (n = 1); dysregulated diabetes (n = 1). After subsequent treatment CE-D and CE-IM was achieved in 97% and 87%, respectively. In 10% a stenosis developed during additional treatment requiring a median of one dilation. CONCLUSION: This study shows that circumferential RFA using the 360 Express may shorten procedure time, while maintaining efficacy compared to standard circumferential RFA.